Evaluation of the effect of nifedipine upon myocardial perfusion and contractility using cardiac magnetic resonance imaging and tissue Doppler echocardiography in systemic sclerosis. Issue 9 (11th February 2005) - Vignaux, O; Allanore, Y; Meune, C; Pascal, O; Duboc, D; Weber, S; Legmann, P; Kahan, A
Abstract : Background: Primary myocardial involvement due to microcirculation impairment is common in systemic sclerosis (SSc). Cardiovascular magnetic resonance imaging (MRI) and tissue Doppler echocardiography (TDE) were recently shown to be more sensitive than conventional methods for the respective assessment of myocardial perfusion and contractility. Previous studies have suggested that dihydropyridine-type calcium channel blockers mitigate both myocardial perfusion and function abnormalities. Objective: To investigate the effects of nifedipine on myocardial perfusion by MRI and on contractility by TDE, in patients with SSc. Patients and methods: 18 patients with SSc without clinical heart failure and with normal pulmonary arterial pressure (14 women, 4 men; mean (SD) age 59 (9) years; mean (SD) disease duration 7 (4) years, 10 with diffuse and 8 with limited cutaneous forms) were prospectively evaluated. The MRI perfusion index, determined from time-intensity curves, and systolic and diastolic strain rate determined by TDE were assessed at baseline, after a 72 hour vasodilator washout period, and after 14 days of oral treatment with nifedipine 60 mg/day. Results: Nifedipine treatment led to a significant increase in the MRI perfusion index (mean (SD) 0.26 (0.07) v 0.19 (0.05) at baseline, p = 0.0003) and in systolic and diastolic strain rate (2.3 (0.6) v 1.5 (0.4) s −1 at baseline, p = 0.0002, and 4.2 (1.6) v 3.0 (1.2) at baseline, p = 0.0003, respectively). Conclusion: Fourteen days of treatment with nifedipine simultaneously improves myocardial perfusion and function, as evaluated by highly sensitive and quantitative methods.